The Correlation between Students’ Socioeconomic Status and Their Motivation in Learning English - Julianti Sapta Nadilla; Chairil Anwar Korompot; Amra Ariyani (Journal of Excellence in English Language Education, 2023)
The purpose of this research is to determine students' socioeconomic status, motivation to learn English, and the relationship between students' socioeconomic status and motivation to learn English. The researchers used correlational research to achieve this goal, and the participants in this study were 22 students chosen using a random sampling technique. This study's findings were gathered using two types of questionnaires. The results revealed that the majority of the students had a moderate socioeconomic status with 10 (45%) students, only 2 (9%) students having a very high level, 8 (36%) students having a low level. and 1 (4.5%) student for high and very low levels, for their motivation in learning English, the majority of students (45%) are in low levels, and there is a strong relationship between students' socioeconomic status and their social status. The correlation between motivation to learn English and motivation to learn English is 0.75. The in-person product-moment retest score ranges from 0.60 to 0.799 indicating a strong category.